Light, Sound and Fragrance: The Impact of Sufism on the Aesthetics of Traditional Malay Literature (Malay Literature, 2011)
Sufi ideas exerted a great influence on nearly every aspect of traditional Malay literature of the late 16th to the 17th century. Not only Malay literary practice of that age owed much to the Sufi inspiration, equally important is the fact that Sufism brought to life a pre-modern Malay literary theory including, inter alia, fundamental concepts of literary aesthetics. On the basis of a poem by Hamzah Fansuri and Sufi allegories Hikayat Inderaputera and Hikayat Si Burung Pingai the article investigates the Sufi doctrine of imagination as a particular world all of its own, the "aesthetics of light" expressed through specific illumination of portrayed events and "lighting effects", and the "aesthetics of ecstasy" communicated through acoustic and olfactory images. By embodying these aesthetics in the "flesh and blood" of literary works, their creators not only managed to reveal Sufi doctrines with more clarity and beauty, but also let their audience experience them both intellectually and emotionally.Keyword: Sufism, Hamzah Fansuri, literary aesthetic, Hikayat Metaphysics.